Entrenchment and the Psychology of Language Learning: How We Reorganize and Adapt Linguistic Knowledge. 2017
DOI: 10.1037/15969-011
|View full text |Cite
|
Sign up to set email alerts
|

Statistical learning as a domain-general mechanism of entrenchment.

Abstract: The birth of the statistical learning literature is often traced back to Reberʼs (1967) seminal study on implicit learning using an artificial grammar learning paradigm. However, to fully understand the relationship between such early implicit learning studies and the current notion of statistical learning, it is important also to consider its conception. The theory of perceptual learning by J. J. Gibson and Gibson (1955) paved the way for accounts of learning with a basis in sensory experience. In the Gibsons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
2
8
0
1
Order By: Relevance
“…Although the exploration of performance in visual AGL is quite extensive, the investigation of the deficit in implicit sequential learning in other modalities of sequential stimuli in AGL task is still at its infancy. The focus on one modality is based on the original assumption of implicit sequential learning as a modal (Jost & Christiansen, ; Reber, ), an is in line with evidence among TD participants which reported above chance learning similar to the results observed in the visual AGL task in various auditory stimuli (spoken syllables (Gomez, ), spoken letters (Manza & Reber, ), sung syllables (Schön et al, ), pure tones (Altmann et al, ; Saffran, Johnson, Aslin, & Newport, ), and musical timbres (Tillmann & McAdams, ). Nevertheless, studies that focused on the effect of modality on performance in an AGL task showed that implicit sequential learning is indeed affected by the modality of the stimuli.…”
Section: Introductionmentioning
confidence: 64%
“…Although the exploration of performance in visual AGL is quite extensive, the investigation of the deficit in implicit sequential learning in other modalities of sequential stimuli in AGL task is still at its infancy. The focus on one modality is based on the original assumption of implicit sequential learning as a modal (Jost & Christiansen, ; Reber, ), an is in line with evidence among TD participants which reported above chance learning similar to the results observed in the visual AGL task in various auditory stimuli (spoken syllables (Gomez, ), spoken letters (Manza & Reber, ), sung syllables (Schön et al, ), pure tones (Altmann et al, ; Saffran, Johnson, Aslin, & Newport, ), and musical timbres (Tillmann & McAdams, ). Nevertheless, studies that focused on the effect of modality on performance in an AGL task showed that implicit sequential learning is indeed affected by the modality of the stimuli.…”
Section: Introductionmentioning
confidence: 64%
“…They also highlight that BROCANTO has provided a useful window onto the neurobiology of grammar learning; however, given that BROCANTO is an artificially constructed language withtypicallyno associated meaning, it is not possible to compare behavioural and neural findings with those reported in native speakers. Further, differences in language learning may be explained by more domain-general mechanisms, such as statistical learning ability (Erickson & Thiessen, 2015;Frost, Armstrong & Christiansen, 2019;Jost & Christiansen, 2017), over and above that of LAA.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, evidence has amassed documenting the extent to which language cognition depends on learning spatiotemporal regularities in a probabilistic manner (Jost & Christensen, 2017). Recent studies highlight the existence of individual differences within this ability (Kidd, Donnelly, & Christiansen, 2018) and discuss the possibility that statistical learning might not be a unitary learning mechanism but a set of domain‐general computational principles that operate in different modalities (Frost, Armstrong, Siegelman, & Christiansen, 2015).…”
Section: Introductionmentioning
confidence: 99%